Obstetric Performance of Women with Advanced Maternal Age in Ahmadu Bello University Teaching Hospital, Zaria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Consequent upon changes in social norms over the years, there has been an increase in the age of marriage and childbirth in women. The older parturient poses a great challenge to the managing obstetrician and a greater challenge to attaining safe motherhood.Aim:To determine the obstetric performance and complications developed during pregnancy and delivery of women with advanced maternal age.Settings and Design:This was a retrospective (case–control) study.Setting:This study was conducted in an ANC and labour ward of ABUTH, Zaria, Nigeria.Materials and Methods:The antenatal and delivery records of women with advanced maternal age (≥35 years) and those within 20–25 years of age from 2002 to 2006 were reviewed. Records of 294 women with advanced maternal age, and 322 of those aged 20–25 years were used.Results:A total of 57% of women with advanced maternal age developed complications compared with 24% in those aged 20–25 years. A total of 13% had chronic hypertension, while 26.2% had pregnancy-induced hypertension. Labour was augmented in 12.2% of those who had spontaneous vertex delivery and 6.2% had EMLSC/S. Low birth weight babies occurred in 11.6% necessitating admission into the SCBU and 5.4% had stillborn.Conclusion:This shows the considerable risk in pregnancies of women with advanced maternal age. It is recommended that to minimise complications; preconception care, antenatal care and skilled attendant at delivery are paramount.